Pathological And Cultural Characteristics Of Different Isolates Of Xanthomonas Axonopodis Pv. Malvacearum (Journal of Plant Disease Sciences, 2022)
Bacterial blight caused by Xanthomonas axonopodis pv. malvacearum infects nearly all crop stages and results in significant loss in cotton yield, seed index, oil percentage and ginning out turn. Bacterium pathogenic, cultural and biochemical variability were assessed in the laboratory, and the results revealed that the isolates Xam-2, Xam-5 and Xam-8 were the most virulent of the tested isolates. In terms of cultural and biochemical tests,the bacterium was gram negative, rod shaped and produced mucoid colonies that were slightly raised, circular, light to dark yellow colour, on NA medium. Showed positive results in KOH solubility, starch hydrolysis, catalase, gelatine liquefaction, tolerance to salt 1% test and negative to indole and methyl red test.
Keywords: Bacterial blight; Cotton; X. axonopodis pv. malvacearum